NO–IL-6/10–IL-1β axis: a new pathway in steatotic and non-steatotic liver grafts from brain-dead donor rats - Casillas-Ramírez, Araní; Micó-Carnero, Marc; Sánchez-González, Alfredo; Maroto-Serrat, Cristina; Trostchansky, Andrés; Peralta, Carmen (Frontiers in Immunology, 2023)
Brain death (BD) and steatosis are both risk factors for organ dysfunction or failure in liver transplantation (LT). Here, we examine the role of interleukin 6 (IL-6) and IL-10 in LT of both nonsteatotic and steatotic liver recovered from donors after brain death (DBDs), as well as the molecular signaling pathways underlying effects of such cytokines. BD reduced IL-6 levels only in nonsteatotic grafts, and diminished IL-10 levels only in steatotic ones. In both types, BD increased IL-1β, which was associated with hepatic inflammation and damage. IL-6 administration reduced IL-1β only in non-steatotic grafts and protected them against damage and inflammation. Concordantly, IL-1β inhibition via treatment with an IL-1 receptor antagonist caused the same benefits in nonsteatotic grafts. Treatment with IL-10 decreased IL-1β only in steatotic grafts and reduced injury and inflammation specifically in this grafts. Blockading the IL-1β effects also reduced damage and inflammation in steatotic grafts. Also, blockade of IL-1β action diminished hepatic cAMP in both type of livers, and this was associated with a reduction in liver injury and inflammation, then pointing to IL-1β regulates cAMP generation in conditions of LT and BD. Additionally, the involvement of nitric oxide (NO) in the effects of interleukins was evaluated. Pharmacological inhibition of NO in LT from DBDs provoked even more evident reductions of IL-6 or IL-10 in non-steatotic and steatotic grafts, respectively. This exacerbated the high levels of IL-1β seen in LT from DBDs, causing worse damage and inflammation in both graft types. The administration of NO donors to non-steatotic grafts potentiated the beneficial effects of endogenous NO, since it increased IL-6 levels, and reduced IL-1β, inflammation, and damage. However, treatment with NO donors in steatotic grafts did not modify IL-10 or IL-1β levels, but induced more injurious effects than the induction of BD alone, characterized by increased nitrotyrosine, lipid peroxidation, inflammation, and hepatic damage. Our study thus highlights the specificity of new signaling pathways in LT from DBDs: NO-IL-6-IL-1β in non-steatotic livers and NO-IL-10-IL-1β in steatotic ones. This opens up new therapeutic targets that could be useful in clinical LT.